PENGARUH PENAMBAHAN PROBIOTIK HERBAL PADA RANSUM TERHADAP PERFORMENT ITIK PEDAGING - Endah Subekti; Dewi Hastuti (Universitas Wahid Hasyim, 2015)
The experiment was conducted to determine the effect of probiotics in diet on performance ( feed consumption, weight gain, and feed conversion) of ducks. Two hundred of day old ducks were divided into five dietary treatments. Each treatment was replicated four times with ten ducks per replicate. The five dietary treatments were P0 (diet without the addition of probiotics), P1 (diet plus probiotics 5 ml/l), P2 (diet plus probiotics 10 ml/l), P3 (diet plus probiotics 15 ml/l) and P4 (diet plus probiotics 20 ml/l). Five dietary treatments and drinking water were given ad libitum. The collected data were analysed using analysis variance of completely randomized design and continued by Duncan’s New Multiple Range Test if analysis of the variance indicated significant difference. The result showed that addition of probiotic levels in diet on duck was significantly different on weight gain and feed conversion ratio of duck. Diet with probiotic 15 ml/l (P3) resulted good performance of duck. It gave an average weight of 1,366 g, 2.07 feed conversion and feed consumtion 2,829 for six weeks.Keywords: Duck, Probiotic, Performance.